Effects of vitamin D supplementation on intestinal permeability, cathelicidin and disease markers in Crohn's disease: Results from a randomised double‐blind placebo‐controlled study. Issue 3 (1st June 2015) - Raftery, Tara; Martineau, Adrian R; Greiller, Claire L; Ghosh, Subrata; McNamara, Deirdre; Bennett, Kathleen; Meddings, Jon; O'Sullivan, Maria
Abstract : Background: Vitamin D (vitD) supplementation may prolong remission in Crohn's disease (CD); however, the clinical efficacy and mechanisms are unclear. Aim: To determine changes in intestinal permeability (IP), antimicrobial peptide (AMP) concentrations and disease markers in CD, in response to vitD supplementation. Methods: In a double‐blind randomised placebo‐controlled study, we assigned 27 CD patients in remission to 2000 IU/day vitD or placebo for 3 mos. We determined IP, plasma cathelicidin (LL‐37 in ng/mL), human‐beta‐defensin‐2 (hBD2 in pg/mL), disease activity (Crohn's Disease Activity Index (CDAI)), C‐reactive protein (CRP in mg/L), fecal calprotectin (µg/g), Quality of Life (QoL) and serum 25‐hydroxyvitamin D (25(OH)D in nmol/L) at 0 and 3 mos. Results: At 3 mos., 25(OH)D concentrations were significantly higher in those whom were treated ( p < 0.001). Intra‐group analysis showed increased LL‐37 concentrations ( p = 0.050) and maintenance of IP measures in the treated group. In contrast, in the placebo group, the small bowel ( p = 0.018) and gastro‐duodenal permeability ( p = 0.030) increased from baseline. At 3 mos., patients with 25(OH)D ≥ 75 nmol/L had significantly lower CRP ( p = 0.019), higher QoL ( p = 0.037), higher LL‐37 concentrations ( p < 0.001) and non‐significantly lower CDAI scores ( p = 0.082), compared to those with levels <75 nmol/L. Conclusion: Short‐term treatment with 2000 IU/day vitD significantly increased 25(OH)D levels in CD patients in remission and it was associated with increased LL‐37 concentrations and maintenance of IP. Achieving 25(OH)D ≥ 75 nmol/l was accompanied by higher circulating LL‐37, higher QoL scores and reduced CRP. Registered at ClinicalTrials.gov (NCT01792388).